The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.4314/evj.v24i2.5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, organ distribution and antimicrobial susceptibility profile of Salmonella isolated from chickens purchased from markets in selected districts of West Shoa, Ethiopia

Abstract: Salmonella is one of the major causes of heavy losses in chicken and foodborne diseases worldwide. The current study was conducted from  November 2015 to May 2016 to estimate the prevalence of Salmonella and determine the antimicrobial susceptibility of isolates in chickens. Chickens (n=205) were purchased from local markets of five selected districts of West Shoa Zone, Central Ethiopia. Following clinical examination, chicken were euthanized and 2-3 ml of blood sample was collected immediately. Then after pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The sample-level prevalence of Salmonella was 6.4% in the current study, which is higher than similar studies in Adama and Modjo towns (2.8%), Central Ethiopia (4.7%), and in and around Modjo and Central Oromia [ 2 , 5 , 23 ]. However, it is lower than the 19% prevalence reported from West Showa, Ethiopia [ 24 ] (Sarba et al). Such variation could be due to factors such as differences in detection methods employed, farm biosecurity level, and hygienic practices in the farms.…”
Section: Discussionmentioning
confidence: 70%
“…The sample-level prevalence of Salmonella was 6.4% in the current study, which is higher than similar studies in Adama and Modjo towns (2.8%), Central Ethiopia (4.7%), and in and around Modjo and Central Oromia [ 2 , 5 , 23 ]. However, it is lower than the 19% prevalence reported from West Showa, Ethiopia [ 24 ] (Sarba et al). Such variation could be due to factors such as differences in detection methods employed, farm biosecurity level, and hygienic practices in the farms.…”
Section: Discussionmentioning
confidence: 70%
“…The worldwide increase of food‐borne infections with antibiotic resistant pathogens is of growing concern and is designated by the World Health Organization (WHO) as an emerging public health problem (CDC, 2006 ; Dagnew et al., 2020 ; Lynch et al., 2006 ; Much et al., 2007 ). Different studies revealed that Salmonella serotypes isolated from foods of animal origin have multidrug resistance with resistance to ≥3 antimicrobial classes (Molla et al., 2003 ; Sarba et al., 2020 ). Globally, Salmonella exhibits extensive resistance profiles, which have been associated with higher rates of morbidity and mortality and costs associated with disease (Angulo et al., 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…In Ethiopia, β-lactam antibiotics, i.e., ampicillin, amoxicillin and penicillin are the most widely used class of medicines to treat respiratory tract infections, prostatitis, urinary tract infections, skin, and soft tissue infections of sensitive bacteria in poultry production [11][12][13]. High level of antibiotic residues were detected in meat and milk in studies conducted in Addis Ababa, Bishoftu, and Adama major cities in the country by microbiological or screening methods [14].…”
Section: Introductionmentioning
confidence: 99%